Design, synthesis and evaluation of MCH receptor 1 antagonists—Part III: Discovery of pre-clinical development candidate BI 186908. Issue 16 (15th August 2015) - Oost, Thorsten; Heckel, Armin; Kley, Jörg T.; Lehmann, Thorsten; Müller, Stephan; Roth, Gerald J.; Rudolf, Klaus; Arndt, Kirsten; Budzinski, Ralph; Lenter, Martin; Lotz, Ralf R.H.; Maier, Gerd-Michael; et al.
Graphical abstract: Abstract: Although overweight and obesity are highly prevalent conditions, options to treat them are still very limited. As part of our search for safe and effective MCH-R1 antagonists for the treatment of obesity, two series of pyridones and pyridazinones were evaluated. Optimization was aimed at improving DMPK properties by increasing metabolic stability and improving the safety profile by reducing inhibition of the hERG channel and reducing the potential to induce phospholipidosis. Steric shielding of a labile keto moiety with an ortho -methyl group and fine-tuning of the polarity in several parts of the molecule resulted in BI 186908 (11g ), a potent and selective MCH-R1 antagonist with favorable DMPK and CMC properties. Chronic administration of BI 186908 resulted in significant body weight reduction comparable to sibutramine in a 4 week diet-induced obesity model in rats. Based on its favorable safety profile, BI 186908 was advanced to pre-clinical development.